Reciprocal modulation of Aβ42 aggregation by copper and homocysteine - Keskitalo, Salla; Farkas, Melinda; Hanenberg, Michael; Szodorai, Anita; Kulic, Luka; Semmler, Alexander; Weller, Michael; Nitsch, Roger M.; Linnebank, Michael (Frontiers in Aging Neuroscience, 2014)
Hyperhomocysteinemia is a risk factor for Alzheimer’s disease (AD). Both homocysteine and Aβ, which accumulates in the brain of AD patients, bind copper. Aim of this study was to test the hypothesis that the association of homocysteine and AD results from a molecular interaction between homocysteine and Aβ that is mediated by copper. We established a microtiter plate format thioflavin T aggregation assay to monitor Aβ42 fibrillization. Copper (5 µM) completely prevented Aβ42 (5 µM) fibrillization. Homocysteine in the absence of copper did not impact Aβ42 fibrillization, but physiological concentrations of homocysteine (10-100 µM) attenuated the inhibitory effect of copper on Aβ42 fibril formation. These results were qualitatively confirmed by electron microscopy, which did not reveal morphological differences. To compare the toxicity of fibrillar and non-fibrillar Aβ42 exposed to copper or homocysteine, rat primary cortical neurons were treated in vitro with 5 µM Aβ42 for 72 hours. After incubation with 5 µM Aβ42 that had been aggregating in the absence of homocysteine or copper, cell viability was reduced to 40%. Incubation with 5 µM Aβ42, in which fibril formation had been prevented or reverted by the addition of 5 µM copper, resulted in cell viability of approximately 25%. Accordingly, viability was reduced to 25% after incubation with 5 µM monomeric, i.e. non-fibrillized, Aβ42. The addition of homocysteine plus copper to 5 µM Aβ42 yielded 50% viability. In conclusion, copper prevents and reverts Aβ fibril formation leading rather to formation of lower order oligomers or amorphous aggregates, and homocysteine reduces these effects. Such mechanisms may explain the association of hyperhomocysteinemia and AD, leading to novel therapeutic strategies in the prevention and treatment of this disease.